Sustainability crises are crises of relationship: Learning from Nyikina ecology and ethics. Issue 4 (5th October 2020) - Milgin, Annie; Nardea, Linda; Grey, Hilda; Laborde, Sarah; Jackson, Sue
Abstract: In the context of the current global ecological and climate crisis, there are increasing calls in the environmental sustainability literature to recognize the validity and value of Indigenous knowledge systems. At the same time, the limitations of utilitarian frameworks of environmental decision‐making are becoming clearer to many researchers and practitioners, who see a need to engage with the underlying ethical questions of sustainability, such as 'What is to be sustained, and for the benefit of which forms of life?' At the interface between these two urgent imperatives, lies a question that has remained marginal in the sustainability literature: How can the environmental ethics of Indigenous societies help frame sustainability science and practice? Based on a case study from Nyikina Country in northern Australia, we show here how the ethical principles embedded in an Indigenous hydro‐ecological knowledge system can help reframe, and address, sustainability crises as crises of relationships. Learning from the linkages between custodial and hydro‐ecological relationships in Nyikina Country, we discuss three contributions of relational thinking to sustainability research and practice. First, at a governance level, the need to embed ontological plurality into state environmental policy. Second, at a management level, the priority of continued communication between the Country and its custodians. Third, at the level of knowledge production, the imperative for sustainability researchers and practitioners to bring to their research process the relational qualities of pluralism, reciprocity and care that are at the core of Nyikina and other Indigenous ecological ethics. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.